Traditio et Translatio Studien zur lateinischen Bibel zu Ehren von Roger Gryson - Bauer, Thomas Johann (Vetus Latina, 2016)
The contributions of the volume give an insight into the different facets of the work of the Vetus Latina Institute Beuron, which was conducted between 1999 and 2014 by Roger Gryson and shaped by his personality. They document the manifold effort and concern of the institute and its staff not only for the remains of the Old Latin Bible, but also for traditio and translatio. The Institute knows how much it owes and owes to Roger Gryson in this field and devotes the present Festschrift to him.